Women understanding of preconception care: How much do they know? - Samsudin, Suhaiza; Md Aris, Mohd Aznan (Partridge, 2018)
Preconception care is an allocation of a set of health education to women and couples before pregnancy and it aims to improve the health status of the mother before pregnancy thus reducing maternal and child mortality. The aim of this study is to measure the level of preconception care knowledge among reproductive age women attending maternal health care. A cross-sectional study was conducted among reproductive women attending Klinik Kesihatan Beserah using a convenience sampling method. A self-administered validated questionnaire was used for data collection. Data were analysed using SPSS software version 24. The study found that majority of women participated in this research has satisfactory level of understanding of preconception care. The mean (SD) score of knowledge was 12.2(3.9). The study also found that level of knowledge was significantly associated with level of education, employment status and total household income. Results from this study indicate that there is a need to enhance preconception care knowledge to reproductive age women, particularly those from low socio economic status. A misconception regarding balanced diet during pregnancy state must be conveyed during delivering of the education.